Early blood-brain barrier disruption in ischemic stroke initiates multifocally around capillaries/venules - Hoffmann, Angelika; Dege, Tassilo; Kunze, Reiner; Ernst, Anne-Sophie; Lorenz, Holger; Böhler, Laura-Inés; Korff, Thomas; Marti, Hugo; Heiland, Sabine; Bendszus, Martin; Helluy, Xavier; Pham, Mirko (Stroke, 2018)
Background and Purpose—Detection and localization of the early phase of blood-brain barrier disruption (BBBD) in vivo during cerebral ischemia/reperfusion injury remain a major challenge but may be a relevant outcome parameter in stroke.Methods—We studied early BBBD in mice after transient middle cerebral artery occlusion by multimodal, high-field (9.4T) in vivo magnetic resonance imaging, including the contrast agent gadofluorineM as an albumin-binding tracer. GadofluorineM contrast-enhanced magnetic resonance imaging was performed to determine BBBD at 2, 6, and 24 hours after reperfusion. BBBD was confirmed and localized along the microvascular tree by using fluorescent gadofluorineM and immunofluorescence stainings (cluster of differentiation 31, ephrin type-B receptor 4, alpha smooth muscle actin, ionized calcium binding adaptor molecule 1).Results—GadofluorineM contrast-enhanced magnetic resonance imaging revealed a multifocal spatial distribution of early BBBD and its close association with the microvasculature at a resolution of 40 μm. GadofluorineM leakage was closely associated with ephrin type-B receptor 4-positive but not alpha smooth muscle actin-positive vessels. The multifocal pattern of early BBBD (already at 2 hours after reperfusion) thus occurred in the distal capillary and venular microvascular bed. These multifocal zones showed distinct imaging signs indicative of early vasogenic edema. The total volume of multifocal early BBBD accurately predicted infarct size at 24 hours after reperfusion.Conclusions—Early BBBD in focal cerebral ischemia initiates multifocally in the distal capillary and venular bed of the cerebral microvasculature. It is closely associated with perimicrovascular vasogenic edema and microglial activation and predicts the extent of final infarction.
Gesehen am 04.03.2020